Amine‐bis(phenolate) Iron(III)‐Catalyzed Formal Hydroamination of Olefins. Issue 7 (1st March 2016) - Zhu, Kailong; Shaver, Michael P.; Thomas, Stephen P.
Abstract: A practical synthesis of highly functionalized amines by the formal hydroamination reaction of alkenes with nitroarenes catalyzed by an air stable amine‐bis(phenolate) iron(III) complex is reported. The reaction uses an easily handled silane, low catalyst loadings, and mild reaction conditions. A wide range of substrates are transformed with synthetically useful yields (21 examples). Abstract : Three for the price of 1 : A simple amine‐bis(phenolate) iron(III) complex catalyzed the formal hydroamination of alkenes with nitroarenes using low catalyst loading at room temperature. A wide range of substrates were tolerated with good yields (21 examples, up to 76 % yield).